(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Stunting and thinness are major nutritional problems affecting adolescents in the developing countries. This cross- sectional study was conducted to identify food consumption pattern, nutritional status and lifestyle pattern of adolescents studying in public schools of Malangwa municipality, Sarlahi, Nepal. MATERIALS AND METHODS: Analytical cross-sectional study was carried out among adolescents of public schools. A semi-structured questionnaire was developed and face to face interview method was used to collect information from three public schools of Malangwa municipality. Simple random sampling technique was applied. Food consumption pattern were reviewed by 24 –hour recall method and 7– day food frequency questionnaire. RESULTS: The result indicated that protein rich food intake was very low (29%) among the adolescent’s daily diet and 82% of the respondents took fruits and vegetables in daily diet. 40.1% respondents were found malnourished, out of which 37.5% were and 64.8% were boys while 35.2% were girls. Also, 2.5% were overweight, out of which 50.0% were girls and 50.0% were boys. CONCLUSIONS: Awareness on healthy eating of the adolescents needs to be created to uphold their nutritional status.